PENGARUH LIKUIDITAS, LEVERAGE, PROFITABILITAS, DAN PERTUMBUHAN PERUSAHAAN TERHADAP KEBIJAKAN DIVIDEN PADA PERUSAHAAN MANUFAKTUR SEKTOR FOOD AND BEVERAGE YANG TERDAFTAR DI BEI - Sitorus, Paskah Ria; Sitorus, Jessy Safitri; Siahaan, Anggiat Maruli (Akuntansi Prima, 2022)
Capital Market Issuers in Indonesia are divided into several sectors. One of them is the food and beverage sector. So far the author has not found a research focusing on food and beverage sector manufacturing companies. The method that researcher used in this study is associative quantitative research. About the collection techniques of the data are carried out by collecting financial statement documents from www.idx.co.id in the period 2015 - 2017. To analysis the data, the researcher use method like multiple linear regression, coefficient of determination, t test, F test. The sample in this study were 18 companies with data consisting of 3 years. The sample selection is done by purposive method. The results showed that the ratio of liquidity, leverage, profitability and company growth have significant effect toward dividend policy in Manufacturing Companies Sector Food and Beverage Listed on the IDX in 2015 - 2017 amounting to 45.3%. The independent variable which have a dominant influence is the leverage variable.